PEMILIHAN KUALITAS INDUKAN IKAN KOI MENGGUNAKAN METODE MULTI- OBJECTIVE OPTIMIZATION ON THE BASIS OF RATIO ANALYSIS (MOORA) (STUDI KASUS MOLLY JAYA INDONESIA) - M. Awang Putratama; Sujatmiko, Bambang; Hadi Sucipto; Reza Augusta Jannatul Firdaus (Inovate, 2024)
AbstractThe ornamental fish farming industry in Indonesia has experienced rapid growth in recent years. This isdriven by the high demand for ornamental fish both domestically and abroad. Ornamental fish have highaesthetic value and can be beautiful decorations for homes, offices, and other places. One of the importantfactors in ornamental fish farming is the selection of the right type of fish. The type of fish chosen must besuitable for environmental conditions and have a high selling value. There are many types of ornamentalfish available on the market, so it is necessary to make the right choice to maximize the profits fromornamental fish farming. One of the decision-making methods that can be used to select ornamental fish isMulti-Objective Optimization on the Basis of Ratio Analysis (MOORA).MOORA is an MCDM method used to select the best alternative from several alternatives based on severalcriteria. Molly Jaya Indonesia is a micro-scale company engaged in the ornamental fish cultivation andsales sector, especially freshwater ornamental fish such as molly fish, koi fish, and betta fish. Molly JayaIndonesia is located in Dusun Surowono, Canggu Village, Badas District, Kediri Regency. Initially, MollyJaya Indonesia was a family business and has been passed down to the fourth generation. The name MollyJaya Indonesia was coined in 2018 and in 2019 began to enter the digital business through social media.One of the obstacles faced by Molly Jaya Indonesia is the lack of efficiency in selecting broodstock with aquality level that has been predetermined, because the sorting procedure in selecting these fish is still donemanually, which requires extra care and patience to identify the fish one by one. Therefore, knowledge isSistem Pendukung Keputusan Pemilihan Indukan Ikan Koi Menggunakan Metode Multi-ObjectiveOptimization On The Basis Of Ratio Analysis (MOORA) (studi kasus Molly Jaya Indonesia)191needed in the selection of koi fish that will be used as broodstock. There are many criteria that can beconsidered in the selection, including the type of koi fish, the shape of the fish's body, the number of colorsand patterns, the age of the fish, and the physical integrity of the fish whether there are any defects or not.This research aims to create an application that helps Molly Jaya Indonesia to determine the koi fish thatwill be used as broodstock by entering the criteria that have been set. Then the data is processed andgraded or ranked using the MOORA (Multi-Objective Optimization On The Basis Of Ratio Analysis)method. This system is expected to be useful to improve efficient and effective performance.Kata Kunci: koi, moora, quality